TREES AS A FORM OF HOPE IN THE CREATION OF MIXED MEDIA ARTWORKS - Tegar Jaka Purnama; Bahari, Nooryan (Institut Seni Indoensia Surakarta, 2024)
Trees as a Form of Hope in The Creation of Mixed Media Artworks. The creation of the artwork started with an idea with trees as the source of inspiration. The great interest in trees occurs because trees are extraordinary creatures with various types and benefits for humans, trees are so close, so the interest continues to grow. Departing from a great interest and the experience of exploring mountainous areas as direct observation by seeing and observing trees, which are diverse and have never been seen before. Trees with a lot of uniqueness not only provide oxygen and shade, in many cultures, trees are considered symbols of life, peace, or immortality, they are even a place to reflect. This creation emphasizes the creation of works with the theme of paintings that show representations of the meaning and beauty of trees. The creation of the work also focuses on paintings that contain the hope that awareness of trees will continue to grow so that the existence of trees can always be maintained. The form of this work is in the form of a two-dimensional work, which uses the grisaille brush technique and graphic art high print technique, however, it is poured into one medium, namely canvas. The realization of the painting is based on an idea and concept found, then designed, then visualized into the process of work, finally realized into one work measuring 80 x 100 cm with the title “The Only One”. In the finishing stage, the work is coated with liquid varnish, this layer protects the surface of the work from dust, dirt, moisture, scratches, and other damage.